Review of the molecular background of self-incompatibility in rosaceous fruit trees - J. Halász; A. Hegedűs; A. Pedryc (International Journal of Horticultural Science, 2006)
This review gives a presentation of the gametophytic self-incompatibility system in the roscaeous fruit trees. Studies to discover the pistil (S-ribonucleases) and pollen-part components (F-box molecules) are summarized and models for the self-incompatibility reactions as well as their molecular background are discussed. We describe how mutations within the S-RNase or F-box genes can contribute to the transition from self-incompatibility to the self-compatible phenotype in many fruit tree crops. The current state of the arts is compared to the information obtained in other plant species possessing similar incompatibility system.